The RNA chaperone, Hfq, controls two luxR-type regulators and plays a key role in pathogenesis and production of antibiotics in Serratia sp. ATCC 39006 - Wilf, N.; Williamson, N.; Ramsay, Joshua; Poulter, S.; Bandyra, K.; Salmond, G. (2011)
Serratia sp. ATCC 39006 (S39006) is a Gram-negative bacterium that is virulent in plant (potato) and animal (Caenorhabditis elegans) models. It produces two secondary metabolite antibiotics, a prodigiosin and a carbapenem, and the exoenzymes, pectate lyase and cellulase. A complex regulatory network that includes quorum sensing (QS) controls production of prodigiosin. While many aspects of the regulation of the metabolites and exoenzymes are well understood, the potential role in this network of the RNA chaperone Hfq and dependent small regulatory RNAs has not been characterized. Hfq is an RNA chaperone involved in post-transcriptional regulation that plays a key role in stress response and virulence in diverse bacterial species. To explore whether Hfq-dependent processes might contribute to the regulation of antibiotic production we constructed an S39006 ?hfq mutant. Production of prodigiosin and carbapenem was abolished in this mutant strain, while production of the QS signalling molecule, butanoyl homoserine lactone (BHL), was unaffected. Using transcriptional fusions, we found that Hfq regulates the QS response regulators, SmaR and CarR. Additionally, exoenzyme production and swimming motility were decreased in a ?hfq mutant, and virulence was attenuated in potato and C. elegans models. These results suggest that an Hfq-dependent pathway is involved in the regulation of virulence and secondary metabolite production in S39006. © 2011 Society for Applied Microbiology and Blackwell Publishing Ltd.